KONSUMSI PANGAN ORGANIK: MENINGKATKAN KESEHATAN KONSUMEN? - Ryna Parlyna; Munawaroh Munawaroh (Jurnal Ilmiah Econosains, 2011)
ABSTRACT Organic food defines as food which contains no hazardous chemical materials as pesticides. In simple word, organic food is a natural food. The organic food industry is rising significantly. Organic rice, organic milk, organic vegetables, organic fruits are some of the examples of the current famous organic foods among consumers. Consuming organic foods protect ones from breast cancer, heart disease and any other serious illness; it can even help people life longer 25 days for man and 17 days for woman. Organic foods are sweeter and tastier than an organic foods.Keywords: Consumption, Organic Foods, health